Insights into determinants influencing food security in the IGAD region of Eastern Africa - Omay, Paulino Omoj; Bahaga, Titike Kassa; Fidar, Abdi (Frontiers in Nutrition, 2025)
BackgroundFood security in the Intergovernmental Authority on Development (IGAD) region of Eastern Africa is affected by a complex interplay of climatic and non-climatic factors. This study explores the major determinants of food security in the region, including extreme climate events (droughts and floods), land use, population growth, food production, market dynamics, and political and economic stability.MethodsThe study employed a combination of descriptive and analytical approaches. Climatic data were derived from CHIRPS (1981–2023) to assess drought and flood patterns using the Standardized Precipitation Index (SPI). Non-climatic data, including population statistics, land availability, food production, trade data, and price trends, were sourced from FAOSTAT. The graphical data illustration, correlation analysis was conducted to examine the temporal patterns and relationships between food security determinants and outcomes such as cereal production, food prices, and undernourishment.ResultsFindings reveal that droughts and extreme wet conditions significantly impact food security outcomes across IGAD countries. Rainfall and arable land showed the strongest positive correlation with cereal production. However, despite vast land resources, countries like Sudan and South Sudan have not fully utilized their agricultural potential. Population growth, unbalanced trade policies, and limited investment in agriculture contribute to high food prices and undernutrition. The correlation analysis indicates that economic stability and population dynamics are key influencers of food production and accessibility. Urban–rural population imbalances and policy gaps further exacerbate food insecurity risks.ConclusionThis study highlights the urgent need for a multi-sectoral and regionally coordinated approach to enhance food security in the IGAD region. Strategies should focus on climate-resilient agriculture, sustainable land management, inclusive economic policies, and food system innovations. Regional cooperation, targeted investments, and context-specific policy interventions are essential to reduce vulnerability and achieve sustainable food security.